Analisis Gerak Tari Piriang Rantak Kudo di Pauh IX Lapau Munggu Kecamatan Kuranji Kota Padang - Lapeni Pebria Maibur; Herlinda Mansyur (SENDRATASIK UNP, 2022)
This research aims to describe and analyze the analysis of Tari Piriang Rantak Kudo movements in Pauh IX Lapau Munggu Kuranji District of Padang City. This type of research is qualitative research with descriptive methods. The object of this research is Tari Piriang Rantak Kudo in Pauh IX Lapau Munggu Kuranji District, Padang City. This research instrument is the researcher himself using stationery and cameras. The types of data used are primary data and secondary data. Data collection techniques include library studies, observations, interviews, and documentation. The steps of this data analysis technique are data collection, data reduction, data presentation, and data verification/conclusion. The results of this study showed that piriang Rantak Kudo dance motion analysis was seen from the aspect of space, elements of time, and energy characteristics. Parts of space have five components, namely line, volume, direction, level, and focus of view. The time aspect has two elements, namely tempo and rhythm. Meanwhile, the power aspect has three components: intensity, pressure, and quality. In the movement piriang Rantak Kudo dance has 9 varieties, namely having 9 movements, namely: 1)the movement of the leader; 2)the movement of the balimau; 3)the movement of bakirok; 4)the movement of sauak sabalah; 5)the movement of ramo-ramo bagaluik; 6)the movement of kirok langkah alai; 7)the movement of langkah alai, 8)the movement of ramo-ramo bagaluik langkah gantuang; 9)closing motion. This aspect of space, time, and energy is essential in motion. Because of the element of space, time, and power, dancers can find out the energy expended in the movement of Tari Piriang Rantak Kudo.